2016
DOI: 10.1021/acsami.6b05629
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Thermal and Upper Voltage Performance of Ni-Rich Cathode Material by a Homogeneous and Facile Coating Method: Spray-Drying Coating with Nano-Al2O3

Abstract: The electrochemical performance of Ni-rich cathode material at high temperature (>50 °C) and upper voltage operation (>4.3 V) is a challenge for next-generation lithium-ion batteries (LIBs) because of the rapid capacity degradation over cycling. Here we report improved performance of LiNi0.8Co0.15Al0.05O2 materials via a LiAlO2 coating, which was prepared from a Ni0.80Co0.15Al0.05(OH)2 precursor by spray-drying coating with nano-Al2O3. Investigations by X-ray diffraction, scanning electron microscopy, energy-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(84 citation statements)
references
References 56 publications
2
78
0
Order By: Relevance
“…However, insufficient energy density due to the limited lithium utilization (<60 %) in the structure of LCO, as well as the high cost of cobalt, restricts its broad applications in stationary energy storage and electric vehicles (EVs) . Hence, intensive researches have been implemented, which focus on developing alternative cathode materials with higher lithium utilization and larger energy density, to expand the application field of LIBs . Furthermore, LIBs for grid‐level energy storage and EVs are expected to offer low cost, superior safety and fast charging .…”
Section: Introductionmentioning
confidence: 99%
“…However, insufficient energy density due to the limited lithium utilization (<60 %) in the structure of LCO, as well as the high cost of cobalt, restricts its broad applications in stationary energy storage and electric vehicles (EVs) . Hence, intensive researches have been implemented, which focus on developing alternative cathode materials with higher lithium utilization and larger energy density, to expand the application field of LIBs . Furthermore, LIBs for grid‐level energy storage and EVs are expected to offer low cost, superior safety and fast charging .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, synthesis of high surface area structures such as nanorod arrays or porous nanosheet 3D structures of LiCoO 2 have been carried out to achieve fast intercalation kinetics and flexible Li‐ion batteries. However, since many degradation mechanisms including the parasitic oxygen release reaction, are surface and subsurface originated, various approaches such as coating, surface passivation, synthesis of core–shell structures and chemical gradient compositions have been pursued for improving the cyclability and stability of cathode materials. For instance, it has been shown that coating the LiCoO 2 cathodes with Al, F‐based material that forms a Li‐Co‐Al‐F‐O solid solution beneath the surface can improve the structural stability of LCO when operating at 4.6 V. Similarly, AlPO 4 coating on LiCoO 2 has shown to effectively prevent the oxygen release reaction and inhibit the over‐charge induced thermal runaway reaction .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the use of surface modification methods (LiCo 2 9, 10 , Al 2 O 3 11 , LiMnPO 4 3 , ZnO 12 , FeF 3 13 , TiO 2 14 ,) can effectively solve the above-mentioned problems. The coating layer prevents the contact of the active material with the electrolyte.…”
Section: Introductionmentioning
confidence: 99%